4°C and beyond: what did this mean for biodiversity in the past - Willis, K; Bennett, K; Bhagwat, S; Birks, H (Taylor and Francis, 2010)
How do the predicted climate changes (IPCC, 2007) for the next century compare in magnitude and rate to those that Earth has previously encountered? Are there comparable intervals of rapid rates of temperature change, sea-level rise and levels of atmospheric CO₂ that can be used as analogues to assess possible biotic responses to future change? Or are we stepping into the great unknown? This perspective article focuses on intervals in time in the fossil record when atmosphere CO₂ concentrations increased up to 1200 ppmv, temperatures in mid- to high-latitudes increased by greater than 4°C within 60 years, and sea levels rose by up to 3 m higher than present. For these intervals in time, case studies of past biotic responses are presented to demonstrate the scale and impact of the magnitude and rate of such climate changes on biodiversity. We argue that although the underlying mechanisms responsible for these past changes in climate were very different (i.e. natural processes rather than anthropogenic), the rates and magnitude of climate change are similar to those predicted for the future and therefore potentially relevant to understanding future biotic response. What emerges from these past records is evidence for rapid community turnover, migrations, development of novel ecosystems and thresholds from one stable ecosystem state to another, but there is very little evidence for broad-scale extinctions due to a warming world. Based on this evidence from the fossil record, we make four recommendations for future climate-change integrated conservation strategies.